2015
DOI: 10.1177/0267659115621614
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of emboli removal by integrated versus non-integrated arterial filters in new generation oxygenators

Abstract: The new generation Sorin Inspire 6 M, with a stand-alone 20 µm arterial filter, appeared most efficient at removing incoming emboli from the circuit. No firm conclusions can be drawn about the relative efficacy of emboli removal by units categorised by class (integrated vs non-integrated); however, the stand-alone 20 µm arterial filter presently sets a contemporary standard against which other configurations of equipment can be judged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…150 mL, may lead to an improved clinical outcome. 11 Recently, Jabur et al 19 compared air removal rates of integrated and non-integrated oxygenator-filter combinations in a clinical setting. They also included the Sorin 6F M, the Capiox FX25 and the Fusion devices.…”
Section: Discussionmentioning
confidence: 99%
“…150 mL, may lead to an improved clinical outcome. 11 Recently, Jabur et al 19 compared air removal rates of integrated and non-integrated oxygenator-filter combinations in a clinical setting. They also included the Sorin 6F M, the Capiox FX25 and the Fusion devices.…”
Section: Discussionmentioning
confidence: 99%
“…[18] A recent study reported that the oxygenators without integrated filters exhibited the highest degree of emboli-trapping capabilities, although they found no disadvantage for oxygenators with integrated filters. [19] The present study compared newly emerging embolic foci in cerebral diffusion-weighted MRI studies pre-and postoperatively in patients undergoing CABG using oxygenators with or without integrated arterial filters. Cerebral silent infarctions known to occur after cardiac procedures can be readily detected using diffusion-weighted MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The technological breakthrough of the HLM was challenged by a number of technological and biological umprecedented problems related to the new interactions between machines and the human body. New materials and new technology resulted in sophisticated devices incorporating better pump heads, biocompatible surfaces for cardiopulmonary bypass tubing aiming at reducing inflammatory response [24] , multiple in-line sensors for better safety, more effective and less traumatic oxygenators with superior performance [25] , in-line filters of all kinds [26,27] , hemoadsorbers [28] and other complements that allowed safer conduct of cardiopulmonary bypass for repair of cardiac disease.…”
Section: The Challenges and The Frontiermentioning
confidence: 99%